Menyingkap Religiositas Hikayat Hang Tuah Melalui Penggunaan Kosakata Islamiah: Kajian Manuskrip Sastra Pendidikan pada Era Merdeka Belajar - Risdiawati, Dian; Nugroho, Faizal Hadi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Hikayat Hang Tuah is actually written in Arabic-Malay script. In addition, the vocabulary used in it is not a little that comes from Arabic. The romance of Islamic Malay culture also seems thick in every story. Thus, it is interesting to conduct a study whose purpose is to describe the form of Islamic Malay/Islamic Malay cultured vocabulary in terms of lexical and grammatical meanings and to describe the religiosity of the vocabulary in the Hikayat Hang Tuah. This research uses qualitative research with philological research approach. The data from this study are the results of the researchers' notes, in the form of vocabulary and entries that form the background of the vocabulary in the saga. While the source of data in this study is the Hikayat Hang Tuah I in 2010 published by the Language Center of the Ministry of National Education. The instrument used in this research is a vocabulary classification guide as well as a rubric for collecting and analyzing data. The results of the study revealed that there were at least 77 data found based on lexical and grammatical meanings. This meaning then shows the existence of Islamic religiosity in the form of Islamic faith which is still influenced by the existence of gods, honorifics of the king which states that the king is a descendant of gods and "representatives of God" in the world and litotes on figures who have lower degrees, work related to religion. Islam, the authority of the king, the equation, and the typical expression of the hikayat.